DESAIN PENELITIAN TINDAKAN KELAS - Rahmah; Dina Hermina; Salamah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Classroom Action Research (CAR) is a type of research conducted by teachers in their own classrooms to improve and enhance the quality of learning continuously. CAR is carried out because there are still various problems in the teaching and learning process, such as low student participation, lack of learning motivation, unsatisfactory learning outcomes, and the use of less effective teaching methods. This study aims to explain the definition of Classroom Action Research, its objectives and benefits, its characteristics and principles, as well as the design and stages of its implementation. The method used in this study is library research with a qualitative approach through collecting data from books, scientific journals, and references related to Classroom Action Research. The results of the study indicate that CAR has an important role in improving the quality of learning through the stages of planning, action, observation, and reflection carried out repeatedly. CAR not only helps improve student learning outcomes, but also enhances teacher professionalism, reflective abilities, and the quality of education in schools. In addition, CAR is in line with Islamic values that emphasize the importance of change, self-evaluation, and the development of knowledge. Therefore, Classroom Action Research becomes a systematic effort that teachers can apply to create more effective, active, and high-quality learning processes.